2018
DOI: 10.1016/j.jece.2018.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-stannosilicate heterogeneous catalyst for biodiesel production using edible, non-edible and waste oils as feedstock

Abstract: Edible and non-edible lipid feedstocks A B S T R A C TThis study reports the synthesis, physicochemical characterization by X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and solid-state MAS NMR ( 1 H, 23 Na, 29 Si and 119 Sn MAS NMR) of a metallo-stannosilicate and its application as a heterogeneous catalyst for biodiesel production via ethanolysis and methanolysis routes using edible, non-edible an waste oils as feedstocks. XRD characterization of the metallo-stannosilicate has revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…This study is a sequence of previous work reported by the authors research group 16 concerning the application of a metallo-stannosilicate for biodiesel production using edible, nonedible and waste oils as feedstocks. In this paper, several stannosilicates were synthesized using different sol-gel chemical compositions.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This study is a sequence of previous work reported by the authors research group 16 concerning the application of a metallo-stannosilicate for biodiesel production using edible, nonedible and waste oils as feedstocks. In this paper, several stannosilicates were synthesized using different sol-gel chemical compositions.…”
Section: Introductionmentioning
confidence: 96%
“…Mixed framework OPT materials containing coordinated tetrahedra or octahedra, namely stannosilicates, is one of these materials subject of research. Stannosilicates and tin-zeotypes materials have been reported as ion exchangers, sorbents and catalysts for several types of reaction, as purification of natural gas with sulfur compounds, like hydrogen sulfides or oxysulfides 11 , and catalytic reactions for decomposition of propan-2ol and oxidation of cyclohexene 12 , Baeyer-Villiger oxidation reactions 13 , monosaccharide isomerization reactions 14,15 and application as heterogeneous catalysts for biofuels production 16 . Tin-based homogeneous and heterogeneous catalysts have been used in transesterification reactions, mainly using refined edible oils as feedstocks and methanol, typically providing high yields of fatty acid methyl esters (FAMEs) [17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%